Defence responses of non-mycorrhizal and mycorrhizal seedlings of Pinus sylvestris L. to fungal pathogens - Bonello, P; Bonello, Pierluigi (1991)
﻿ The defence mechanisms expressed in roots of Pinus sylvestris seedlings challenged with fungal pathogens were investigated, and a comparison was made between the expression of defences in non-mycorrhizal and mycorrhizal seedlings. Papillae were formed by cortical cells of non-mycorrhizal seedlings infected with Cylindrocarpon destructans. Histochemical evidence was obtained for pectic materials comprising an important polysaccharide component of these structures, and for the deposition of polyphenolic compounds also. Proton induced X-ray emission (PIXE) microanalysis indicated that insoluble calcium levels were elevated in papillae relative to normal cell walls. Although papillae appeared important in protecting cortical cells against penetration by fungal hyphae, a primary role for the wall appositions in the resistance of seedlings of Scots pine against root pathogens could not be proven. Although phytoalexins were not detected in the roots of Scots pine seedlings following infection with C. destructans, the mean content of an abietic acid fraction (comprising six compounds, of which only dehydroabietic acid could be positively identified), increased from 5.2 to 9.7mg g-1 dry weight. This fraction exhibited some antifungal activity. -related proteins induced de novo by infection could not be detected, but several constitutive apoplastic proteins, including some with chitinase activity, appeared to increase in the needles of root-infected seedlings. The formation of ectomycorrhizae with Pisolithus tinctorius, Suillus bovinus and Hebeloma crustuliniforme did not itself induce papilla formation in the roots of P. sylvestris. Evidence was obtained to suggest that the response was suppressed when mycorrhizal seedlings were challenged with C. destructans. Results highly suggestive of the induction of systemic resistance in P. sylvestris seedlings, consequent upon mycorrhizal infection, were obtained. In seedlings grown in vitro the survival rate of mycorrhizal seedlings challenged aerially with Botrytis cinerea was 37.5% compared with 7.1 in seedlings grown gnotobiotically. However, the physiological mechanisms by which this protection was imparted remain to be determined.